Achieving Surgical, Obstetric, Trauma, and Anesthesia (SOTA) care for all in South Asia - Zadey, Siddhesh; Rao, Shirish; Gondi, Isha; Sheneman, Natalie; Patil, Chaitrali; Nayan, Anveshi; Iyer, Himanshu; Kumar, Arti Raj; Prasad, Arun; Finley, G. Allen; Prasad, Chellapuram Raja Krishna; Chintamani,; et al. (Frontiers in Public Health, 2024)
South Asia is a demographically crucial, economically aspiring, and socio-culturally diverse region in the world. The region contributes to a large burden of surgically-treatable disease conditions. A large number of people in South Asia cannot access safe and affordable surgical, obstetric, trauma, and anesthesia (SOTA) care when in need. Yet, attention to the region in Global Surgery and Global Health is limited. Here, we assess the status of SOTA care in South Asia. We summarize the evidence on SOTA care indicators and planning. Region-wide, as well as country-specific challenges are highlighted. We also discuss potential directions—initiatives and innovations—toward addressing these challenges. Local partnerships, sustained research and advocacy efforts, and politics can be aligned with evidence-based policymaking and health planning to achieve equitable SOTA care access in the South Asian region under the South Asian Association for Regional Cooperation (SAARC).